Test Pit Excavation within Currently Occupied Rural Settlements in the Czech Republic, Netherlands, Poland and United Kingdom – Results of the Care Project in 2022/23 - Lewis, Carenza; Vařeka, Pavel; Van Londen , Heleen; Verspay, Johan; Marciniak, Arkadiusz; Kajda, Kornelia; Kobiałka, Dawid (Medieval Settlement Research, 2023)
2022–23 was the final full year of the ‘Community Archaeological in Rural Environments Meeting Societal Challenges’ (CARE-MSoC) project, which was granted an extension to compensate for delays caused to the test pit excavation programme in 2020 and 2021 by the COVID-19 pandemic. The extension enabled fieldwork to take place in the Netherlands, Czech Republic and UK (Fig. 1). 120 test pits were excavated and the results of these are summarised here as an update to previous reports in Medieval Settlement Research reviewing the outcomes of nearly 200 test pits excavated in 2019 and 2020 (Lewis et al. 2020; 2021; 2022a). The reviews published here in Medieval Settlement Research focus on information pertaining to the historic development of medieval rural settlements. The CARE project has also investigated the social impact of public participation in local research-driven archaeological investigation, and data pertaining to this have also been collected, analysed and published in journals focussed on heritage and health (e.g. Lewis et al. 2022b; Brizi et al. 2023).